Type 1 fimbriae are important factors limiting the dissemination and colonization of mice by Salmonella Enteritidis and contribute to the induction of intestinal inflammation during Salmonella invasion - Kuźmińska-Bajor, Marta; Grzymajło, Krzysztof; Ugorski, Maciej (Frontiers in Microbiology, 2015)
We have recently shown that S. Gallinarum type 1 fimbriae with endogenous mannose-resistant (MR) variant of the FimH protein increase systemic dissemination of S. Gallinarum and colonization of internal organs in comparison to the S. Gallinarum fimH knockout strain or the mutant expressing mannose-sensitive (MS) FimH variant from S. Enteritidis. Elaborating from these studies, we proposed that MS variants of FimH are advantageous in gastrointestinal infections, in contrast to MR FimH variants which decrease intestinal colonization and promote their systemic spreading. To support our hypothesis, we carried out in vivo studies using mice infected with wild type S. Enteritidis and its fimH knockout strain (S.Enteritidis fimH::kan), which was characterized by significantly lower adhesion and invasiveness of murine ICE-1 intestinal cells. Using bioluminescence imaging, we observed that the loss of MS FimH adhesin correlates well with the highly increased colonization of mice by these bacteria. The appearance of the mutant strain was observed much earlier than wild-type Salmonella, and mice infected with 104–107 S.Enteritidis fimH::kan CFUs had significantly (P<0.05) shorter infection-free time than animals inoculated with wild type S. Enteritidis. Infections caused by non-typhoid Salmonella, such as S. Enteritidis, are associated with massive inflammation of the lamina propria and lymph nodes in the intestinal tract. Therefore, we evaluated the role of MS type 1 fimbriae in the induction of cytokine expression and secretion, using murine ICE-1 intestinal cells. We showed that the expression, as well as secretion, of Il-1B, Il-6, Il-10 and Il-12b was significantly higher in cells infected with wild type S. Enteritidis compared to cells infected with the mutant strain. Based on our results, we propose that type 1 fimbriae may play an important role in the pathogenicity of S. Enteritidis and may contribute to an intestinal inflammatory response.